STUDY ON THE PRACTICES EVALUATIONS IMPLEMENTED IN THE SCHOOL PHYSICAL EDUCATION AND YOUR RELATIONSHIP WITH THE CYCLES OF PROFESSIONAL DEVELOPMENT (Fiep Bulletin - online, 2015)
The human being development as a whole and, especially in the professional ambit, it usually happens through phases or cycles, which can interfere in the professional performance. In this perspective, to present research it tried to identify the characteristics of the evaluation process implemented in the School physical education considering the cycles of the teachers' professional development. Besides, the teachers' profile was verified in relation to the aspects that tell respect the: gender, age, title, work regime and time of work. For so much, she opted to use a descriptive-interpretative methodology with a qualitative approach of the data. The participants consisted of teachers that supply classes in the public and private schools of the municipal district of Marechal Cândido Rondon - Pr, in the school period of the year of 2005. The instrument used in the collection of the data it consisted of semi-structured interview. The questions that orientated the interviews were open, to obtain varied answers on the practices evaluations. For the analysis of the data, the teachers were contained considering the cycles of professional development. The results evidenced that most of the investigated teachers if he/she found in the consolidation cycles and diversification. In what he/she refers to the cycles of professional development and the relationship with the evaluation tendencies that orientate the practices evaluations, the predominance of teachers of the consolidation cycle was observed in the tendency humanist and of the diversification cycle in the traditional tendency of evaluation.
Keywords: .